Análisis Financiero a la Cooperativa de Ahorro y Crédito Economía del Sur ECOSUR, del Cantón Saraguro, periodos 2020 – 2021. - Piedra González, Monica Cecibel (2024)
The Curricular Integration Work called "Financial Analysis of the Cooperativa de Ahorro y Crédito Economía del Sur ECOSUR, Cantón Saraguro, period 2020 - 2021", was developed with the purpose of fulfilling the proposed objectives, trying to analyze the economic and financial situation of the cooperative. In order to accomplish the above, the vertical and horizontal analysis of the financial statements was performed. In the vertical analysis is shown that within the Assets the most representative account is the Credit Portfolio with $ 938.298,69 corresponding to 79,59%, for the year 2021, due to the products that are capitalized in the approval of the different loans within the cooperative; among the Current Liabilities the most outstanding account is Obligations with the Public with $ 1.030.071,29 equivalent to 94,84%, in 2020 and $ 1.296.633,95 equivalent to 97,39%, for the year 2021, related to demand deposits and time deposits, which are executed by all members of the cooperative. The horizontal analysis indicates the variations of increases or decreases of each value in the accounts of the Financial Statements denoting that for the year 2021 there was an increase in all groups of Assets, Liabilities, Equity and Income, thus it is understood that the cooperative is being adequately financed. Then the financial indicators were applied highlighting that the Structure and Quality of Assets showed a growth in the assets, indicating an effective placement of resources in productive assets. Finally, the financial report was elaborated, presenting the results according to the applied analysis, conclusions and recommendations related to the economic and financial situation of the cooperative, which will guide to the managers to make better decisions for the growth of the cooperative.